Pengaruh promosi perpustakaan melalui media sosial instagram terhadap minat kunjung pemustaka di Perpustakaan Universitas Mercu Buana Yogyakarta - Sarah Wulan Dari; Sri Rohyanti Zulaikha (Al-Kuttab : Jurnal Kajian Perpustakaan, Informasi dan Kearsipan, 2023)
This study aims to determine the effect of library promotion through Instagram social media on visitor interest using the AIDA model. The research method in this research is quantitative-descriptive. The population in this study were students who came to visit the library, while the sampling technique used was incidental sampling, with a sample of 25 respondents. Meanwhile, the data collection technique is a questionnaire that uses a Likert scale with five alternative answers. Testing the validity of the data using the validity test using product moment correlation and for reliability testing using Cronbach's alpha and to see the effect between the two variables using correlation tests and simple linear regression. The data was processed using the IBM SPSS Statistics version 26 program. The results showed that there was a promotion effect on visitor interest at the correlation level, namely the number 0.484 which indicates the moderate category at the coefficient interval of 0.40-0.599. This influence certainly occurs because every student already has an Instagram account and has followed the official UMBY campus Instagram account and the UMBY library Instagram account, so information dissemination can easily occur within the student environment.